KONSTRUKSI ISU LINGKUNGAN DALAM NOVEL ANAK MATA DAN MANUSIA LAUT: KAJIAN EKOKRITIK DAN IMPLIKASINYA TERHADAP LITERASI EKOLOGIS - Nur Fajriati, Tanzilia; Sidiq, Burhan; Nur Afiati, Laksmita; Sukandar, Ricky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Examining environmental issues in children's literature is crucial, as it plays an important role in shaping values, sensitivity, and ecological reasoning. This study aims to analyze the construction of environmental issues in the children's novel Mata dan Manusia Laut by Okky Madasari and to formulate its implications for strengthening ecological literacy. Employing a descriptive qualitative method, the study utilizes an ecocritical approach and narrative structure analysis. The findings reveal that environmental issues in the novel are constructed through five patterns: relational, ecological conflict, local ethics, corrective, and pedagogical. These patterns are developed through the interplay of characters, setting, conflict, and plot, representing the human–environment relationship while supporting the development of ecological literacy across the dimensions of knowledge, attitudes, culture, and reflection. This study contributes to the advancement of ecocritical studies in children's literature and provides a conceptual foundation for ecological literacy-based literature instruction in schools.